Early Breast Angiosarcoma Development After Radiotherapy: A Cautionary Tale. Issue 2 (August 2019) - Wei, Nicholas J. J.; Crowley, Timothy P.; Ragbir, Maniram
Abstract : Abstract: This is a short clinical report depicting an exceptionally early presentation of radiation-induced angiosarcoma and overview of the literature. This case highlights the need for a high level of clinical suspicion in those patients presenting with unresolving cutaneous skin changes after radiotherapy for breast cancer. Breast-conserving therapy, comprising breast-conserving surgery and adjuvant radiotherapy, has largely replaced mastectomy in the treatment of early-stage breast carcinoma. Breast angiosarcoma is a rare but severe long-term complication associated with postoperative radiotherapy ( Int J Radiat Oncol Biol Phys . 2002;52:1231–1237). It often presents as a bluish/purple skin lesion in a breast previously treated for breast cancer. This case explores an unexpectedly early presentation of radiation-induced breast angiosarcoma, which was initially thought to be benign bruising. Management remains challenging and prognosis is poor because of its aggressive local and regional invasion and early metastasis, commonly to the lungs and liver. Early surgical resection with wide margins is the treatment of choice ( J Plast Reconstr Aesthet Surg . 2011;64:1036–1042). Abstract : Supplemental digital content is available in the text.